الخصائص المورفومترية لحفر الإذابة في منطقة غور الحديثة - الساحل الشرقي للبحر الميت - القرالة، محمد جميل أحمد; الروسان، نايف محمود عبدالله (جامعة مؤتة, 2011)
تهدف هذه الدراسة إلى دراسة الخصائص المورفومترية لحفر الإذابة، وتوزعها في غور الحديثة على طول الساحل الشرقي للبحر الميت. ونتيجة لانخفاض منسوب سطح البحر الميت ظهر مئات من حفر الإذابة الإنهيارية تسببت في تدمير البنية التحتية، والمزارع. وتشكل حفر الإذابة مظاهر هبوط أرضي، تحدث نتيجة انتقال المياه الجوفية في ممرات أرضية ناتجة عن عملية الإذابة الناتجة عن انحسار البحر الميت. تم إجراء عمل ميداني في منطقة الدراسة، واستخدم نظام التوقيع العالمي GPS لتحديد بعض مواقع حفر الإذابة المتوفرة في المنطقة. وتم اشتقاق الخارطة الطبوغرافية، والخارطة الجيولوجية بواسطة عملية الترقيم باستخدام برنامج ARC/ VIEW3.2. وأجري التحليل المورفومتري ل 18 حفرة إذابة، بلغ قطر أكبرها 30م، بعمق 18م، بشكل شبه دائري، ومتباينة الأحجام. وتوصي الدراسة بوضع حماية حول حفر الإذابة، وتوخي المخططين للأثار المحتملة لحساسية المنطقة للأنشطة التنموية. The aim of this paper is to study the morphometric characteristics of the sinkholes, and its distribution in Ghor AL-Haditaha along the eastern shore of the Dead Sea. Over the past years, the coastal area of the declining Dead Sea has undergone a hundred of catastrophic collapse of sinkholes causing severe damage to the infrastructures and farms. \ Sinkholes area subsidence features, the surface expression of these features is a result of water transporting residual material and soil through pathways established by the dissolution process related to the recession of the Dead Sea. Field work has been carried out in the study area, GPS survey was carried out to define the location of some of available sinkholes in the area, topographic, geological maps derived by digitizing method using ARC/VIEW3.2 software, morphometric analyses of 18 sinkholes showed that the largest is a much as 30m in diameter and 18m in deep, forming a close circular shape and vary in size resulted of sudden collapse. The sinkholes in the study caused serious damage to the infrastructures and farms. Thus, the study recommended buffers around sinkholes, and land managers should be sensitive to the potential impact of any land development activities in the area.
Keywords: حفر الإذابة -- الأردن -- الغور الحديث -- البحر الميت -- التحليل المورفومتري -- الخصائص المورفومترية -- الخرائط -- الجيولوجيا -- الطبوغرافيا -- التضاريس -- الصخور -- التربة